Biological Action of Singlet Molecular Oxygen from the Standpoint of Cell Signaling, Injury and Death - Junichi Fujii; Yuya Soma; Yumi Matsuda (Molecules, 2023)
Energy transfer to ground state triplet molecular oxygen results in the generation of singlet molecular oxygen (1O2), which has potent oxidizing ability. Irradiation of light, notably ultraviolet A, to a photosensitizing molecule results in the generation of 1O2, which is thought to play a role in causing skin damage and aging. It should also be noted that 1O2 is a dominant tumoricidal component that is generated during the photodynamic therapy (PDT). While type II photodynamic action generates not only 1O2 but also other reactive species, endoperoxides release pure 1O2 upon mild exposure to heat and, hence, are considered to be beneficial compounds for research purposes. Concerning target molecules, 1O2 preferentially reacts with unsaturated fatty acids to produce lipid peroxidation. Enzymes that contain a reactive cysteine group at the catalytic center are vulnerable to 1O2 exposure. Guanine base in nucleic acids is also susceptible to oxidative modification, and cells carrying DNA with oxidized guanine units may experience mutations. Since 1O2 is produced in various physiological reactions in addition to photodynamic reactions, overcoming technical challenges related to its detection and methods used for its generation would allow its potential functions in biological systems to be better understood.